Optimization of drawing scheduling based on mixed integer programming in block cave mining - REN Zhu-li; BI Lin; WANG Li-guan; CHEN Xin (工程科学学报)
Drawing scheduling is the most important process in block cave mining. The traditional analysis process of drawing scheduling is random and inefficient without system scientific analysis. A mixed integer programming method was proposed in this paper to solve the optimization problem of drawing scheduling. Taking the ore reserve quantity, ore grade, drawing index and production scheduling index as the constraints and the grade fluctuation as the objective function, a drawing scheduling optimization model was built based on the mixed integer programming method. It was solved with the CPLEX solver invoked by model language that was programmed with YALMIP in MATLAB for a certain copper mine. Finally, the optimal arrangement scheme of drawing scheduling was obtained. It is proved that this model is scientific and feasible, the grade fluctuation reduces by 18%, and compared with the traditional, this drawing scheduling saves costs by meeting the desired production quantity more closely and reducing the employee time spent on preparing schedules.